Hyperechoic papillary muscle: A sign of ALCAPA in the presence of left-to-right shunts - Thanigai Arasu; T Komal; Krishnan Ganapathy Subramaniam; Dhruva Sharma; N. Srinath Reddy (Journal of Clinical and Scientific Research)
A 10-month-old female child with failure to thrive was diagnosed to have a large atrial septal defect (ASD) with deficient rims and large patent ductus arteriosus (PDA) and was referred for management. Echocardiography showed normal left ventricular (LV) function with dilated right atrium and right ventricle; the only suspicious finding was that of the hyperechoic papillary muscle. After the PDA ligation, the ASD was closed with an autologous pericardial patch when the aortic cross-clamp was released, the rhythm returned and trans-oesophageal echocardiography showed severe LV dysfunction. While still on the pump, the PA was opened, and the coronary ostia were identified as arising from the non-facing sinus. Coronary reimplantation was done, and then, the patient could be weaned off cardiopulmonary bypass uneventfully, the child was shifted to the intensive care unit with minimal inotropic support and was discharged by the 7th day with normal ventricular function. The presence of an anomalous coronary artery can be masked by the large left-to-right shunts, resulting in PA hypertension. Anomalous left coronary artery from the right pulmonary artery (ALCAPA) should be suspected in the presence of hyperechoic papillary muscles, which could be a sign of papillary muscle ischaemia. ALCAPA can be missed in the presence of significant left-to-right shunts, which increases the pulmonary artery (PA) pressures and the oxygenation of pulmonary arterial blood. We present one such case with large ASD and PDA, with normal LV function and no mitral regurgitation, with the only indicator being hyperechoic papillary muscles.